Decay-Accelerating Factor in Tears of Contact Lens Wearers and Patients with Contact Lens-Associated Complications - Szczotka, Loretta B.; Cocuzzi, Enzo; Medof, M. Edward (Optometry and vision science, 2000)
Complement activation fragments have been detected in the anterior segment during 1) eye closure, 2) contact lens wear, and 3) in some contact lens-associated pathologies. The decay-accelerating factor (DAF), a membrane-associated complement regulatory protein that inhibits the central C3 amplification convertases of the cascade, is present on both the ocular surface and in tears. In this study, we measured levels of tear DAF in asymptomatic contact lens patients and in patients who presented with contact lens-associated complications. Tears were collected from 55 patients using capillary pipettes. Subjects included normal non-contact lens wearing controls (N = 14), asymptomatic soft (N = 13) and rigid gas permeable (N = 5) wearers, and individuals with contact lens-induced acute red eye (CLARE) (N = 4), ulcerative keratitis (N = 3), giant papillary conjunctivitis (GPC) (N = 8), contact lens peripheral ulcers (N = 3), and infiltrative keratitis (N = 5). Levels of DAF were assessed using a two-site immunoradiometric assay using anti-DAF monoclonal antibodies. The mean concentration of DAF in normal controls was found to be 149+/-78 ng/ml, 117+/-59 ng/ml, and 111+/-86 ng/ml for noncontact lens patients, and asymptomatic soft and rigid gas permeable lens wearers, respectively. In the conditions of CLARE, infiltrative keratitis, and GPC, DAF concentrations were significantly reduced compared with normal noncontact lens controls. Compared with asymptomatic soft lens patients, the condition of infiltrative keratitis showed a significant reduction in tear DAF. This study documents a trend toward decreased levels of tear DAF in patients with the contact lens associated inflammatory conditions CLARE, GPC, and infiltrative keratitis. Tears of patients with infiltrates show the most significant reduction of tear DAF. The reductions may be associated with enhanced complement activation contributing to the pathogeneses of infiltrative keratitis and associated ocular surface diseases.